The effect of building height on thermal properties and comfort of a housing project in the hot arid climate of the UAE - Salameh, Muna; Elkhazindar, Ayat; Touqan, Basim (Frontiers in Built Environment, 2023)
Cities' microclimate is greatly impacted by urbanization. The ratio of building height to street width of each structure affects the thermal properties of the urban canyons. This characteristic is one of the main elements that control the thermal radiation emitted and how much solar radiation is absorbed, causing the urban air temperature to be much greater than in rural areas (Urban Heat Island effect). Therefore, the main aim of this study is to examine the thermal effect of the height variation for housing buildings on the urban layout and canyons in the hot arid climate of the UAE. The study used a qualitative method based on ENVI-met software and a case study -an existing housing project - to investigate the current situations and the future thermal conditions for proposed configurations for the housing case study. The study investigated two groups of configurations with unified and diversified heights. The results of the study found that the best case among the first group of configurations with unified heights was U3 – which had unified masses’ heights reach 20m height and with the highest H/W ratio and lowest sky view factor, it recorded 0.5 ˚C reduction in the air temperature compared to the base case at 2:00 p.m. Moreover, the results revealed that in the case of having diversified heights, it is better to locate the highest masses in the hot wind direction, as for D2 - with highest masses with 20m height were located only on the north and west sides of the area blocking the hot north west prevailing wind –the D2 case recorded a reduction about 0.9 ˚C compared to the base case. Moreover, in the cases with lower air temperature U3 and D2 recorded the best predicted mean vote readings, especially in the day time when the air temperature is high.